Evaluating Transparency and Fairness in Booth Registration and Curation Decision-Making at Comic Frontier: A Multi-Method Approach - Penina Annais; Utomo Sarjono Putro (Politeknik Siber Cerdika Internasional, 2026)
Background: The rapid growth of pop culture conventions has intensified competition and heightened expectations for transparent and efficient exhibitor registration systems. Comic Frontier, one of Indonesia's largest pop culture events, has faced recurring exhibitor dissatisfaction concerning booth registration and curation processes. Objective: This study seeks to identify gaps between exhibitor expectations and experiences, determine root causes of complaints, examine best practices from comparable events, and propose strategic improvements for a more effective system. Methods: A mixed-method approach was applied. Quantitative data from 120 respondents were analyzed using gap analysis, ANOVA, and descriptive statistics. Qualitative insights were obtained through 12 semi-structured interviews and two Focus Group Discussions (14 participants), structured using the Kepner-Tregoe method and prioritized via Pareto analysis. Instrument reliability exceeded Cronbach's alpha of 0.70. A weighting matrix assessed the relative impact of root causes. Results: Significant perception gaps were identified, particularly in transparency of curation criteria (mean gap = 1.42) and clarity of registration timelines (mean gap = 1.31). ANOVA revealed significant differences in satisfaction across experience levels (F(2, 117) = 8.74, p < 0.01, η² = 0.13), indicating disproportionate disadvantages for newcomers. Structural constraints—rapid applicant growth versus limited organizational capacity—were identified as primary causes. Benchmarking emphasized structured timelines and clear criteria as critical trust-building mechanisms. Conclusion: The study proposes a structured transparent registration framework as a short-term solution and an integrated digital platform as a long-term strategy. These measures are expected to enhance fairness, reduce uncertainty, and strengthen governance in large-scale cultural event management.